CRISPR/Cas13: A potential therapeutic option of COVID-19 (2020)
The novel coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be considered as the most important current global issue, as it has caused the novel coronavirus disease (COVID-19) pandemic, which has resulted in high mortality and morbidity rates all around the world. Although scientists are trying to discover novel therapies and develop and evaluate various previous treatments, at the time of writing this paper, there was no definite therapy and vaccine for COVID-19. So, as COVID-19 has called ideas for treatment, controlling, and diagnosis, we discussed the application of Clustered Regularly Interspaced Short Palindromic Repeats/Cas13 (CRISPR/Cas13) as a treatment of COVID-19, which received less attention compared with other potential therapeutic options.